Is there new physics around the corner? - Eboli, OJP (Springer, 2000)
There are many theoretical arguments indicating that there should be new Physics around the TeV scale which can be discovered in the next decade. We briefly review some of the possible scenarios which give rise to a plethora of new signals at collider experiments.